Evolution of a filmless digital imaging and communications in medicine-conformant picture archiving and communications system: design issues and lessons learned over the last 3 years...Proccedings of the 16th Symposium for Computer Applications in Radiology. 'PACS: Performance Improvement in Radiology.' Houston TX, May 6-9, 1999 - Henri CJ; Cox RD; Rubin R; Bret PM; Couch GG (Journal of Digital Imaging)
This presentation describes our experience and lessons learned over the first 3 years of developing and operating a filmless picture archiving and communications system (PACS) for all computed tomography (CT), magnetic resonance (MR), ultrasound, and nuclear medicine studies in our hospital. The PACS conforms to the Digital Imaging and Communications in Medicine (DICOM) standard and includes a sophisticated Worldwide Web (WWW)-based interface to complement the regular DICOM services. The PACS has undergone many design modifications from its inception, which have addressed performance, functionality, support, and maintenance issues. The lessons we have learned through making these modifications are described here and may prove to be helpful to anyone planning to deploy a PACS of their own. Copyright (c) 1999 by W.B. Saunders Company